2002
DOI: 10.1016/s1535-6108(02)00045-4
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a signaling directly affects cell motility and invasion of metastatic melanoma

Abstract: Gene expression profiling identified human melanoma cells demonstrating increased cell motility and invasiveness. The gene WNT5A best determined in vitro invasive behavior. Melanoma cells were transfected with vectors constitutively overexpressing Wnt5a. Consistent changes included actin reorganization and increased cell adhesion. No increase in beta-catenin expression or nuclear translocation was observed. There was, however, a dramatic increase in activated PKC. In direct correlation with Wnt5a expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
806
4
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 868 publications
(862 citation statements)
references
References 33 publications
44
806
4
8
Order By: Relevance
“…Although evidence has been accumulated that Wnt5a is expressed in various cancers (Weeraratna et al, 2002;Veeman et al, 2003;Huang et al, 2005;Kurayoshi et al, 2006;Pukrop et al, 2006;Kikuchi and Yamamoto, 2008;Yamamoto et al, 2009), how Wnt5a is upregulated in cancer cells has not been determined. It has been shown that Wnt5a is upregulated at the transcriptional level in PCa by hypomethylation in the 5 0 -untranslated region and that three CpG sites were consistently methylated in normal tissues but not in primary PCa (Wang et al, 2007).…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence has been accumulated that Wnt5a is expressed in various cancers (Weeraratna et al, 2002;Veeman et al, 2003;Huang et al, 2005;Kurayoshi et al, 2006;Pukrop et al, 2006;Kikuchi and Yamamoto, 2008;Yamamoto et al, 2009), how Wnt5a is upregulated in cancer cells has not been determined. It has been shown that Wnt5a is upregulated at the transcriptional level in PCa by hypomethylation in the 5 0 -untranslated region and that three CpG sites were consistently methylated in normal tissues but not in primary PCa (Wang et al, 2007).…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcamentioning
confidence: 99%
“…Wnt5a is a representative of the Wnt proteins that activate the b-catenin-independent pathway, which includes multiple pathways, and Wnt5a activates distinct routes (Veeman et al, 2003;Kurayoshi et al, 2007;Kikuchi and Yamamoto, 2008). It has been shown that Wnt5a stimulates migration in some cancer cells and that its expression is correlated with the aggressiveness of melanoma, breast cancer, lung cancer and gastric cancer (Weeraratna et al, 2002;Veeman et al, 2003;Huang et al, 2005;Kurayoshi et al, 2006;Pukrop et al, 2006;Kikuchi and Yamamoto, 2008;Yamamoto et al, 2009), suggesting that Wnt5a has oncogenic properties. Other reports indicate that Wnt5a acts as a tumor suppressor based on the finding that Wnt5a has an ability to inhibit proliferation, migration and invasiveness in thyroid tumor and colorectal cancer cell lines (Dejmek et al, 2005;Kremenevskaja et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that Wnt5a inhibits cell growth, migration, and invasiveness of thyroid carcinoma cells and colorectal cancer cells (Dejmek et al, 2005;Kremenevskaja et al, 2005). However, there are several lines of evidence indicating that sustained or increased Wnt5a expression is critically involved in various types of cancer (Iozzo et al, 1995;Weeraratna et al, 2002;Kurayoshi et al, 2006;Pukrop et al, 2006). Thus, at present the roles of Wnt5a in human cancers are controversial, although this discrepancy may be attributable to differences in receptor context or cell context of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Ror2 mediates Wnt5a signaling by activating the Wnt/JNK pathway and inhibiting the b-catenin-TCF pathway (Oishi et al, 2003;Mikels and Nusse, 2006). Studies using cultured mammalian cells show that Wnt5a promotes cell migration (Weeraratna et al, 2002;Kodama et al, 2004;Masckauchan et al, 2006), and that Ror2 mediates Wnt5a-induced cell migration through its association with the actin-binding protein, filamin A (Nishita et al, 2006). In addition, it has recently been reported that Wnt5a regulates cell polarity in cooperation with Par/Atypical protein kinase C pathway (Schlessinger et al, 2007), and that Ror2 mediates Wnt5a-induced polarized cell migration by activating JNK through its association with filamin A (Nomachi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…30 Other novel genes that have been detected that were not hitherto implicated in melanomagenesis include WNT5A, a proto-oncogene involved in cell motility; 21 confirmatory application of an antibody that inactivates the wnt5a protein product, termed 'Frizzled-5', arrests the effects of wnt5a. 31 In addition to WNT5A, other genes are implicated in the acquisition of cell motility and angiogenesis. 25,26,[32][33][34] Hypoxia-inducible genes such as Cyr61 have shown to be constitutively upregulated in late stage melanoma.…”
Section: Molecular Adjuncts To Diagnosis: the Microarraymentioning
confidence: 99%